School life during COVID-19: a qualitative study exploring English secondary school staff and pupils’ experiences of the school-based mitigation measures - Sarah Bell; Jane Williams; Sabi Redwood; Jeremy Horwood (BMC Public Health)
Abstract Background In England, the national Government was responsible for balancing the risks of COVID-19 infection, transmission and illness against the known risks of school closures. The Department for Education (DfE) issued guidance to schools, however, there is limited empirical evidence on the experiences of staff and pupils affected by the guidance and accompanying COVID-19 mitigation measures. Methods This qualitative study explored secondary school staff and pupils’ views and experiences of COVID-19 guidance and mitigation measures. There were two main objectives: (i) to examine implementation effectiveness, and (ii) to explore their effectiveness at promoting safety. Participants were purposively sampled from English schools serving diverse communities participating in the CoMMinS (COVID-19 Mapping and Mitigation in Schools) study. Semi-structured interviews were conducted remotely, and data were analysed thematically. Results Interviews took place between January and August 2021 with participants from five secondary schools (20 staff and 25 pupils); staff represented a range of roles within the school and pupil demographics varied. Main themes were: (i) negative views of the DfE guidance; (ii) negative experiences of the DfE guidance; (iii) ineffectiveness of the DfE guidance and school mitigation measures at promoting safety and reducing risk; (iv) ineffective implementation of the mitigation measures due to poor adherence and acceptability (with sub-themes for Lateral Flow Testing (LFT), face coverings, physical distancing and ventilation); and (v) positive perceptions (with sub-themes for hygiene measures, and approaches that facilitated implementation and safety which included staff enforcing compliance, having an ethos of co-operation, addressing inconsistencies, and minimising change). Conclusions Insights from this research will help understand effectiveness of the measures in the ‘real-world school setting’. Understanding the experiences of staff and pupils will help to support policymakers and school leaders in future pandemic decision-making. This research identified challenges with the guidance and measures, minimal impact on perceived safety, and a negative impact on wellbeing. These challenges should be considered when assessing the benefit of the measures in keeping schools safe.